Penerapan Metode Inquiri Untuk Meningkatkan Hasil Belajar Fisika Siswa Pada Materi Besaran Dan Satuan - muntasir muntasir (LEMBAGA PENELITIAN DAN PENGABDIAN MASYARAKAT (LPPM) UNIKS, 2021)
The method was an important factor that needs to be mastered by teachers in carrying out learning in schools. To obtain good student learning outcomes, every teacher should be able to use methods that are in accordance with the material presented. Because not all methods are suitable for every subject matter presented, but there are methods that are more suitable for certain materials and not or less suitable for other materials. One of the efforts that must be done is to find teaching methods that are able to invite students to be more active in learning activities and train students to learn a lot on their own. Based on the background of the problem above, the formulation of the problem in this research is: